Diagnosing scaling bottlenecks in 10 community conservation initiatives in southern and eastern Africa - Thomas Pienkowski; Matt Clark; Arundhati Jagadish; Aklei Albert; Mohanjeet Brar; Tarn Breedveld; Linda Chinangwa; Deepali Gohil; Deziderius Irumba; Ramzy Kanaan; Rose Peter Kicheleri; Phillip Kihumuro; et al. (Conservation Biology, 2026)
Scaling area‐based conservation, including initiatives led or comanaged by Indigenous Peoples and local communities, is a flagship goal of the Kunming‐Montreal Global Biodiversity Framework. Conservationists often aspire to scale initiatives, but this is rarely achieved in practice. Identifying and addressing factors that limit initiative adoption (i.e., bottlenecks) could improve scaling strategies. We used insightsfrom 84 expert surveys to identify potential risk factors and bottlenecks to scaling 10 community, area‐based initiatives in southern and eastern Africa. The number of reported potential risk factors and bottlenecks varied among initiatives. However, unfair benefit sharing, unequal decision‐making, inflexible rules, and top‐down leadership were frequently identified as bottlenecks. Although adopting initiatives had costs (e.g., increased local conflicts, reduced local access to natural resources and cropland), most experts believed these costs were offset by other benefits and thus did not constitute bottlenecks. Our results did not capture local perspectives, but they suggest scaling strategies that strengthen environmental governance may support more socially just and durable approaches to meeting area‐based conservation goals.

Avoiding an impending collision in international conservation - Lovemore Sibanda; Amy Dickman; Courtney Hughes; Jessica Tacey; Emily Madsen; Lessah Mandoloma; Moreangels M. Mbizah; Yolanda Mutinhima; Betty Rono; Salum Kulunge; David Kimaili; Trisha Bhujle; et al. (Conservation Biology, 2025)